2006
DOI: 10.1089/bfm.2006.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Mastitis Symptoms as a Predictor of C-Reactive Protein in Milk and Blood During Lactation

Abstract: Objective: To investigate the presence of C-reactive protein (CRP) in breast milk and any relationship between changes in CRP in breast milk and blood, and the severity of systemic and breast symptoms experienced during mastitis.Methods: Mothers (n ‫؍‬ 26) were followed prospectively from day 5 postpartum to the end of their lactation. Milk from each breast, blood, 24-hour urine samples and data on breast and systemic pathologies were collected at reference intervals during the first 3 months postpartum, daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
1
15
1
1
Order By: Relevance
“…Maternal infections might influence CRP levels in breast milk, but data are sparse. Fetherston et al (2006) reported higher concentrations of CRP in the milk of mothers with mastitis versus those without mastitis and with infective (i.e., bacterial) versus noninfective mastitis. Results also indicated transfer of systemic CRP into breast milk, since milk from the infected and uninfected breasts of the same woman showed no difference in CRP content.…”
Section: Adiponectinmentioning
confidence: 96%
“…Maternal infections might influence CRP levels in breast milk, but data are sparse. Fetherston et al (2006) reported higher concentrations of CRP in the milk of mothers with mastitis versus those without mastitis and with infective (i.e., bacterial) versus noninfective mastitis. Results also indicated transfer of systemic CRP into breast milk, since milk from the infected and uninfected breasts of the same woman showed no difference in CRP content.…”
Section: Adiponectinmentioning
confidence: 96%
“…Based on the literature, 28,29 we expected breastmilk CRP and IL-6 to be low relative to serum. Thus, assays were chosen based on sensitivity and performance in validation experiments using skimmed milk as the test matrix (spike recovery and linearity 80-100% of expected values).…”
Section: Breast Milk Collection and Assaysmentioning
confidence: 99%
“…CRP is an important acute phase protein in humans [37] , dogs [38,39] , horses [40] and pigs [41] . Since peripheral CRP level changes minimally in cows during inflammation [42] it is not generally considered an acute phase protein for cows [42,43] .…”
Section: Discussionmentioning
confidence: 99%